Strategic Leadership of School Administrators Affecting Effectiveness in Management of Schools under Surat Thani Primary Educational Service Area District Office 2 - Jitjamnong, Natthasit; Chimtragoon, Chalermwit; Muongmee, Suchin (Rajapark Journal, 2023)
This research aimed to study 1) study the Strategic Leadership of School Administrators 2) study the effectiveness in the management of schools and 3) study the strategic leadership of school administrators affecting effectiveness in the management of schools under Surat Thani Primary Educational Service Area District Office 2. A sample group consisted of 313 teachers under Surat Thani Primary Educational Service Area District Office 2 of the 2021 Academic year. The research instrument the 5-level estimate rating scale questionnaire. The data analysis statistics were the Frequency, Percentage, Mean, Standard Deviation, and Multiple Linear Regression Analysis. The research findings were: 1) the Strategic leadership of school administrators both overall and each aspect were at high level. 2) the Effectiveness in the management of schools both overall and each aspect were at high level and 3) the Strategic leadership of school administrators affecting effectiveness in the management of schools under Surat Thani Primary Educational Service Area District Office 2 were design and development of organizational culture, communication for strategic implication, developing vision, and revolutionary analytic thinking with the equation as follows. Ŷ = .636 (Constant) + .154X7 + .321X8 +.240X1 +.144 X2